The effect of glutathione addition in sperm diluent on the quality of bovine chilled semen - Endang Triwulaninngsih; P Situmorang; T Sugiarti; R.G Sianturi; D.A Kusumaningrum (Indonesian Center for Animal Research and Development (ICARD), 2003)
This study has been conducted at the Laboratory of Physiology Reproduction, Research Institute for Animal Production (RIAP), Ciawi-Bogor, West Java. Sperms were collected from FH bulls with body weight 613 kg (FH-1) and 480 kg (FH-2) twice a week. Briefly after quality evaluation, semen was diluted in Tris-Citrate buffer medium, containing egg yolk (20% v/v) and (4% v/v) glycerol to get spermatozoa concentration of 50 x 106 per ml. Sperm diluents were added with glutathione (GSH) with doses of 0.0; 0.5; 1.0 and 1.5 mM as treatments A, B, C and D respectively. The diluted semen was then cooled from 35 to 5°C using a cooling machine for 60 minutes then stored in the refrigerator (5°C). Recorded parameters were the survivability of spermatozoa by evaluating the percentage of motile and live, the condition of acrosome and plasma membrane. Data were analysed by completely randomised design with the general linear model (GLM) procedure. The characteristics of collected semen were normal. Viability of spermatozoa stored at 5°C for 0, 1, 4 and 8 days shown by intact acrosomal were 74.42; 69.27; 57.80 and 42.58% for A, B, C and D respectively. Those data were significantly different (P<0.01). Motility, live and intact plasma membrane were 46.72; 52.34; 53.44 and 51.09%; 63.59; 69.11; 68.64; and 66.89%, and 66.01; 69.75; 68.38 and 68.44% for treatment A, B, C and D respectively. Additional 0.5 mM GSH gave the highest (P<0.01) motility, live and intact plasma membrane of sperm. Therefore, it is concluded that the effect of addition 0.5 mM of GSH to the sperm diluents can improve the viability of spermatozoa and possibly protect the spermatozoa from free radical damage. Key words: Glutathione, viability, spermatozoa